A New Method for the Measurement of Gas Pressure in Water-Bearing Coal Seams and Its Application. (19th October 2020) - Cui, Xiao; Zhang, Jiayong; Guo, Liwen; Gong, Xuemin
Abstract : Coal seam gas pressure is one of the fundamental parameters used to assess coal seam gas occurrence and is an important index in assessing the risk of gas disaster. However, the geological characteristics of coal seams become increasingly complex with increasing mining degree, thus decreasing the accuracy and success rate of direct methods for measuring gas pressure. To address such issues, we have developed a new method for direct measurement of gas pressure in water-bearing coal seams. In particular, we developed a pressure measurement device based on theoretical analysis and quantified the basic parameters of the device based on well testing. Then, we verified the applicability of our method based on comparative analysis of the results of field experiments and indirect measurements. Our results demonstrate that this new method can resolve the effects of water pressure, coal slime, and other factors on the estimation of gas pressure. The performance of this new method is considerably better than that of traditional methods. In particular, field test results demonstrate that our method can accurately and efficiently measure gas pressure in water-bearing coal seams. These results will be of great significance in the prevention and control of coal seam gas disaster.